1997
DOI: 10.1074/jbc.272.36.22389
|View full text |Cite
|
Sign up to set email alerts
|

Unaltered Secretion of β-Amyloid Precursor Protein in Gelatinase A (Matrix Metalloproteinase 2)-deficient Mice

Abstract: The ␤-amyloid peptide, which forms extracellular cerebral deposits in Alzheimer's disease, is derived from a large membrane-spanning glycoprotein referred to as the ␤-amyloid precursor protein (APP). The APP is normally cleaved within the ␤-amyloid region by a putative proteinase (␣-secretase) to generate large soluble amino-terminal derivatives of APP, and this event prevents the ␤-amyloid peptide formation. It has been suggested that the gelatinase A (matrix metalloproteinase 2, a 72-kDa type IV collagenase)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
226
2
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 329 publications
(238 citation statements)
references
References 25 publications
8
226
2
2
Order By: Relevance
“…Embryonic fibroblasts from the wild-type mice were injected into the ankle joint on days 0, 3, and 6. These cells secrete MMP-2 in vitro (14). Recovery from the exacerbated arthritis in the MMP-2 KO mice occurred following the injection of wild-type fibroblasts (Fig.…”
Section: Exacerbated Arthritis In Mmp-2 Ko Mice Was Recovered By Mmp-mentioning
confidence: 99%
See 3 more Smart Citations
“…Embryonic fibroblasts from the wild-type mice were injected into the ankle joint on days 0, 3, and 6. These cells secrete MMP-2 in vitro (14). Recovery from the exacerbated arthritis in the MMP-2 KO mice occurred following the injection of wild-type fibroblasts (Fig.…”
Section: Exacerbated Arthritis In Mmp-2 Ko Mice Was Recovered By Mmp-mentioning
confidence: 99%
“…Gelatin zymography was conducted as described previously (14). Briefly, whole mouse paws were removed proximal to the carpus or tarsus and homogenized in 50 mM Tris-HCl (pH 7.5), 150 mM NaCl, and 1% Nonidet P-40 and centrifuged at 15,000 rpm for 10 min.…”
Section: Gelatin Zymographymentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] Gene knockout studies have suggested that the gelatinases may cooperate in vivo. [11][12][13] In this respect, an example may be represented by the process of inflammation, wherein the degranulation of extravasated neutrophils allows MMP2 and MMP9 to share the same extracellular space, thus enhancing the probability to interact with the same substrates. 14 Neutrophil degranulation is associated with the ability of neutrophils to cross basement membranes, composed mainly of a type IV collagen network; 15,16 therefore, the enzymatic activities of MMP2 and MMP9 on type IV collagen are likely relevant for this process.…”
Section: Introductionmentioning
confidence: 99%